The SAM Algorithm for Analogy-Based Story Generation - Ontanon, Santiago; Zhu, Jichen (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2011)
Analogy-based Story Generation (ASG) is a relatively under-explored approach for story generation and computational narrative. In this paper, we present the SAM (Story Analogies through Mapping) algorithm as our attempt to expand the scope and complexity of stories generated by ASG. Comparing with existing work and our prior work, there are two main contributions of SAM: it employs 1) analogical reasoning both at the specific story content and general domain knowledge levels, and 2) temporal reasoning about the story (phase) structure in order to generate more complex stories. We illustrate SAM through a few example stories.